Discrimination, Competition, and Loan Performance in FHA Mortgage Lending - Berkovec, James A.; Canner, Glenn B.; Gabriel, Stuart A.; Hannan, Timothy H. (The Review of Economics and Statistics, 1998)
This study tests for the presence of prejudicial or “noneconomic” discrimination on the part of mortgage lenders by evaluating the performance of home mortgage loans. The approach differs from that of previous studies of loan performance in that it is based on the proposition that noneconomic discrimination should be more pronounced in less competitive lending environments, while statistical discrimination should not. Using a rich set of FHA-insured loan records and measures of local market concentration to proxy the competitive environment, we test for the prediction of better loan performance by minority borrowers relative to white borrowers in more concentrated markets. We argue that this approach substantially reduces the potential for omitted-variable bias that has cast a shadow on previous studies of lending discrimination. Results fail to reject the null hypothesis of no noneconomic discrimination.